Dehydration and volatilization non-isothermic kinetic of the solid state aluminium 8-hydroxyquinolinate - Ribeiro, Clóvis Augusto; Crespi, Marisa Spirandeli; Guerreiro, Cassia Teresa Ramelo; Veronezi, Ana Maria (Eclética Química, 2001)
Al(C9H6ON)3.2.5H2O was precipitated from the mixture of an aqueous solution of aluminium ion and an acid solution of 8-hydroxyquinoline, by increasing the pH value to 9.5 with ammonia aqueous solution. The TG curves in nitrogen atmosphere present mass losses due to dehydration, partial volatilisation (sublimation plus vaporisation) of the anhydrous compound followed by thermal decomposition with the formation of a mixture of carbonaceous and residues. The relation between sublimation and vaporisation depends on the heating rate used. The non isothermic integral isoconventional methods as linear equations of Ozawa-Flynn-Wall and Kissinger-Akahira-Sunose (KAS) were used to obtain the kinetic parameters from TG and DTA curves, respectively. Despite the fact that both dehydration and volatilisation reactions follow the linearity by using both methods, only for the volatilisation reaction the validity condition, 20£ E/RT£ 50, was verified.